Microbial Metabolism of Rofecoxib, A Selective COX-2 Inhibitor - Orabi, Khaled (International Journal of Biotechnology for Wellness Industries, 2013)
Microbial transformation studies of rofecoxib (1), a potent selective cyclooxygenase-2 inhibitor, using sixty microorganisms, mainly fungi and actinomycetes, have revealed that it was metabolized by three microorganisms. Using a standard two-stage screening technique, Cunninghamella echinulata var. echinulata ATCC 9244, Mucor griseocyanus ATCC 1207b, and Rhizopus oryzae ATCC 34121 showed two common more polar metabolites 2 and 3. Moreover, it was apparent that Cunninghamella echinulata var. echinulata was the most efficient microorganism to almost completely metabolize 1, and hence, was selected for preparative scale fermentation. These metabolites were characterized on the basis of their spectral data as 4′-hydroxyrofecoxib (2) and 3′-hydroxyrofecoxib (3).